Plastic After an Extreme Storm: The Typhoon-Induced Response of Micro- and Mesoplastics in Coastal Waters - Nakajima, Ryota; Miyama, Toru; Kitahashi, Tomo; Isobe, Noriyuki; Nagano, Yuriko; Ikuta, Tetsuro; Oguri, Kazumasa; Tsuchiya, Masashi; Yoshida, Takao; Aoki, Kunihiro; Maeda, Yosaku; Kawamura, Kiichiro; et al. (Frontiers in Marine Science, 2022)
Extreme storms, such as tropical cyclones, are responsible for a significant portion of the plastic debris transported from land to sea yet little is known about the storm response of microplastics and other debris in offshore and open waters. To investigate this, we conducted floating plastic surveys in the center of Sagami Bay, Japan approximately 30 km from the coastline, before and after the passage of a typhoon. The concentrations (number of particles/km2) of micro- and mesoplastics were two orders of magnitude higher 1-day after the typhoon than the values recorded pre-typhoon and the mass (g/km2) of plastic particles (sum of micro- and mesoplastics) increased 1,300 times immediately after the storm. However, the remarkably high abundance of micro- and mesoplastics found at 1-day after the typhoon returned to the pre-typhoon levels in just 2 days. Model simulations also suggested that during an extreme storm a significant amount of micro- and mesoplastics can be rapidly swept away from coastal to open waters over a short period of time. To better estimate the annual load of plastics from land to sea it is important to consider the increase in leakages of plastic debris into the ocean associated with extreme storm events.